The Development of Mesoporous Ni‐Based Catalysts and Evaluation of Their Catalytic and Photocatalytic Applications. Issue 12 (26th March 2020) - Kour, Sharanmeet; Mishra, Ankit; Sinha, Anil; Kaur, Pawandeep; Singh, Hari
Abstract: Porous Ni‐based catalysts have attracted extensive attention for a wide range of applications in energy production and environmental remediation due to controllable morphology, high dispersion. These properties are mainly governed by a number of parameters such as compositions, synthesis methods, their structural morphology, and surface area. Various efforts have made to develop unsupported template‐assisted catalysts with specific nanostructures and surface properties, a new approach in supramolecular chemistry. This review reports a detailed overview of the development of mesoporous nickel‐based catalysts for energy and environmental applications. This review also looks at recent advancements, synthesis routes for porous nickel‐based catalysts, and comparative study with the reported Ni‐based catalysts. This review addresses numerous characteristic reactions and processes in the utilization of organic wastes, highlighting the significance of developing porous, proficient, and stable Ni‐based catalysts. Abstract : Obtaining chemicals from biomass and carbon dioxide via catalytic and photocatalytic are attractive routes respectively to achieve sustainable objectives. The review gives an insight into the different methods for the synthesis of porous Ni‐based catalysts. It includes the comparative study of different types of porous Ni‐based catalysts. This review also reports on the developments of different porous Ni‐based catalysts and the evaluation of their catalytic and photocatalytic applications.